The Impact Of Service Quality On Zakat Stakeholders Satisfaction: A Study On Malaysian Zakat In Institutions - Norazlina Abd. Wahab, Ahmad Zubir Ibrahim (Universiti Sains Islam Malaysia, 2017)
Abstract